If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(8n+3)=6(1+n)
We move all terms to the left:
2(8n+3)-(6(1+n))=0
We add all the numbers together, and all the variables
2(8n+3)-(6(n+1))=0
We multiply parentheses
16n-(6(n+1))+6=0
We calculate terms in parentheses: -(6(n+1)), so:We get rid of parentheses
6(n+1)
We multiply parentheses
6n+6
Back to the equation:
-(6n+6)
16n-6n-6+6=0
We add all the numbers together, and all the variables
10n=0
n=0/10
n=0
| (5)/(4v)=(1)/(12)+(7)/(3v) | | 5+2p-2=6p+9-2p | | 4(2x+7)=-29+9 | | 14d^2-11d-3=0 | | 17y+31=150 | | 9n+4=5n | | 0.002(8-k)+0.08(k-2)=1 | | -4(v+2)+2v+7=6v+9 | | x+10°+10=90° | | 2t+2.50+8/100(2t+2.50)=13.80 | | 3p-4+4=2p-14+4 | | 4x+0.7=28.7 | | 12-10x+x=-18 | | 12=6x-6x12=6X-6X12=6x-6x12=6x-6x | | 3x+15=3(-7x+6) | | (9x+7)=(11x-7) | | 62=3d+8 | | 21/bb=2 | | 4/5(30x+20)-5=-1/2(6x-4) | | 3p-4=-2p-14 | | 5r-2=6r+5= | | 4+9(x-3)=7-4(x-3) | | -20=z-3 | | 3x/3=2/5 | | 9(2+v)+36v=14v | | (4+x)+(3x+2)=90 | | 3x=280000 | | 28=9r-8 | | -x-3=21 | | (2d3-6d2+2d-5)-(-d2+7d-2)=0 | | 8x+12+8x+12=13x+38 | | 12=6x-6x12=6x-6x |